Honeycomb carbon sandwich composite panel under compressive load flat-wise: experimental analysis / Ramzyzan Ramly...[et al.] - Ramly, Ramzyzan; Kuntjoro, Wahyu; Ab Ghani, Amir Radzi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
This article is an experimental study of honeycomb core carbon skin sandwich composite panel using American Standards for Testing Materials, ASTM Standards C365/C365M-11a for honeycomb structure flatwise compressive strength. The objective of this article is to describe the process of validation done in the specimens prepared in the research are, to have consistency in terms of the strength and other mechanical properties and to ensure the materials prepared in the lab and can be applied for aviation application (aircraft control surface) later. The samples were prepared in accordance with aviation industry standards using the aviation industry materials at the approved facility (Malaysian Airlines Composite workshop in Subang). The experiment was conducted using the Instron 8802 UTM by following the ASTM Standards at the Faculty of Mechanical Engineering, University Teknologi MARA. From the experiment in accordance with the test standard, the results of the experiment showed the consistency in terms of strength of the specimen. The ultimate strength was found at the average 5.88 kN.